The Effect of Modified Game-Based Learning on Forward Roll Skill Improvement in Elementary School Students - Gilang Rizqi Nursa'ban; Rizal Ahmad Fauzi; Adang Sudrazat (Journal Coaching Education Sports, 2026)
This study investigated the effectiveness of modified game-based learning in improving forward roll skills among elementary school students. Difficulties in performing forward rolls are commonly caused by fear, low confidence, and limited motor coordination. A quasi-experimental pretest-posttest control group design was employed involving 26 students divided into an experimental group (n=13) and a control group (n=13). The experimental group received modified game-based learning, while the control group received conventional instruction. Data were collected using a validated forward roll skill assessment sheet and analyzed using normality, homogeneity, independent sample t-test, and N-Gain analyses. The results revealed a significant difference between the two groups (p < 0.05). The experimental group achieved a higher posttest mean score (90.46) than the control group (73.31). Furthermore, the experimental group obtained an N-Gain score of 82.28% (effective category), while the control group achieved 43.94% (less effective category). These findings indicate that modified game-based learning effectively improves forward roll skills, increases student confidence, and creates a more engaging physical education learning environment.